Medical Costs and Hospitalizations Among Patients with Depression Treated with Adjunctive Atypical Antipsychotic Therapy: An Analysis of Health Insurance Claims Data. (July 2013) - Halpern, Rachel; Nadkarni, Anagha; Kalsekar, Iftekhar; Nguyen, Hiep; Song, Rui; Baker, Ross A; Nelson, J Craig
BACKGROUND: Depression is frequently debilitating. The American Psychiatric Association recommends adjunctive atypical antipsychotics as a treatment option when response to antidepressants is inadequate. OBJECTIVE: To compare medical costs and hospitalizations among patients with depression treated with adjunctive aripiprazole, olanzapine, or quetiapine. METHODS: This retrospective analysis used medical and pharmacy claims data and enrollment information from a large US health plan. Patients were adult members of a commercial health plan who were diagnosed with depression (ie, ICD-9-CM 296.2x, 296.3x, or 311) and who received an antidepressant with adjunctive atypical antipsychotic therapy (aripiprazole, olanzapine, or quetiapine) between January 1, 2004, and January 31, 2010. Patients were continuously enrolled for 6-month pre- and 12-month postaugmentation periods. Those with schizophrenia or bipolar disorder were excluded. Postaugmentation outcomes were total and mental health–related medical costs and hospitalizations. Costs and hospitalizations were modeled with generalized linear models (ie, gamma distribution, log link) and logistic regression, respectively. Regressions controlled for dose, demographics, and general and medical health–related health status. RESULTS: A total of 10, 292 patients were identified across atypical antipsychotic cohorts: 3849 used aripiprazole, 1033 used olanzapine, and 5410 used quetiapine. Mean (SD) age was 44.1 (11.6) years and 70.3% were female. Compared with patients in the aripiprazole cohort, those in the olanzapine cohort had higher total medical costs (cost ratio [CR] 1.22, 95% CI 1.07–1.39) and higher mental health–related medical costs (CR 1.33, 95% CI 1.11–1.59), as well as higher odds of any (total) hospitalization (OR 1.58, 95% CI 1.30–1.92) and any mental health–related hospitalization (OR 1.81, 95% CI 1.38–2.38). Similarly, the quetiapine cohort had higher total medical costs (CR 1.27, 95% CI 1.16–1.39) and higher mental health–related medical costs (CR 1.23, 95% CI 1.09–1.39), as well as higher odds of any (total) hospitalization (OR 1.65, 95% CI 1.44–1.90) and any mental health–related hospitalizations (OR 1.78, 95% CI 1.45–2.18), compared with the aripiprazole cohort. CONCLUSIONS: Compared with adjunctive olanzapine or quetiapine, adjunctive aripiprazole was associated with lower mean total and mental health–related medical costs and with lower odds of total and mental health–related hospitalizations in patients with depression.